Laminated perovskite assembly and preparation method thereof

By designing a specific laser scribe mode in the laminated perovskite assembly, retaining part of the third carrier transport layer and the narrow bandgap perovskite absorption layer, the direct contact problem between the top electrode and the tunneling composite layer is solved, and the filling factor and photoelectric conversion efficiency of the assembly are improved.

CN119730671APending Publication Date: 2025-03-28RENSHUO SOLAR ENERGY (SUZHOU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411924162.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In a stacked perovskite assembly, direct contact between the top electrode and the tunneling composite layer results in degradation of component performance, how to avoid such contact to improve the filling factor and photoelectric conversion efficiency of the component.

Method used

By designing P2-1 scribing, P2-2 scribing and P2-3 scribing, part of the third carrier transport layer and narrow bandgap perovskite absorption layer are retained in the isolation groove, so as to cover the side wall of the tunnel composite layer to avoid direct contact between the top electrode and the tunnel composite layer.

Benefits of technology

The filling factor of the stacked perovskite module is effectively improved, and the photoelectric conversion efficiency of the module is thus improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730671A_ABST
    Figure CN119730671A_ABST
Patent Text Reader

Abstract

The invention provides a laminated perovskite assembly and a preparation method thereof. The preparation method comprises the steps that P1 scribing is conducted, and the transparent bottom electrode is cut off; forming a first carrier transport layer, a wide-band gap perovskite absorption layer and a second carrier transport layer, and performing P2-1 scribing until the transparent bottom electrode is exposed; forming a third carrier transport layer, a tunneling composite layer and a fourth carrier transport layer, and performing P2-2 scribing until the transparent bottom electrode is exposed; the P2-2 lineation line and the P2-1 lineation line at least partially coincide; forming a narrow-band-gap perovskite absorption layer and a fifth carrier transport layer, and performing P2-3 scribing until the transparent bottom electrode is exposed; the projection formed by the lineation of the P2-3 on the horizontal reference surface is located in the internal area range of the projection formed by the lineation of the P2-2 on the horizontal reference surface; and forming a top electrode layer, and carrying out P3 scribing to cut off the top electrode layer. According to the invention, direct contact between the top electrode layer and the tunneling coincidence layer is avoided, and the photoelectric conversion efficiency of the assembly is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells and relates to a perovskite solar cell assembly, in particular to a laminated perovskite assembly and a preparation method thereof. Background Art

[0002] Organic-inorganic hybrid perovskite solar cells have attracted extensive attention from academia and industry due to their many advantages such as adjustable band gap and low cost. At present, the highest photoelectric conversion efficiency of single-junction perovskite solar cells has increased from 3.8% in 2009 to more than 26% in 2024, and the efficiency of perovskite-perovskite double-layer cells exceeds 31%.

[0003] In the preparation process of perovskite components, the laser etching and scribing (P1-P3) process is an important link, among which P1 refers to laser etching on conductive glass such as FTO to form a separate sub-battery module. P2 is to selectively remove the functional layer such as perovskite by laser etching and scribing after the deposition of the perovskite active layer or functional layer, exposing the bottom electrode surface such as FTO. The P2 etching and scribing process provides a channel for the connection between the top electrode and the bottom electrode of the component. Finally, after the top electrode is deposited, P3 etching and scribing is used to block the charge transfer on the top electrode surface, thereby forming a separate sub-battery.

[0004] For stacked perovskite modules, compared with single-junction solar cells, the tunneling layer usually uses inorganic conductive metal oxides such as ITO and IWO. In addition, inert metals such as gold can also be used as tunneling layers. x In addition, after laser P2 scribing of the stacked components, the top electrode (commonly used materials are metals) will come into direct contact with the side of the tunneling layer such as IWO and Au, which can easily cause the performance of the component to deteriorate.

[0005] Therefore, how to avoid direct contact between the top electrode and the tunneling composite layer, thereby effectively improving the filling factor of the stacked perovskite component and further improving the photoelectric conversion efficiency of the stacked perovskite component, is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a laminated perovskite component and a preparation method thereof. The present invention designs P2-1 scribe lines, P2-2 scribe lines and P2-3 scribe lines, thereby retaining at least part of the third carrier transport layer and part of the narrow bandgap perovskite absorption layer in the isolation groove, achieving side wall coverage of the tunneling composite layer, avoiding direct side contact between the subsequently formed top electrode layer and the tunneling conforming layer, effectively improving the filling factor of the laminated perovskite component, and thus improving the photoelectric conversion efficiency of the laminated perovskite component.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a laminated perovskite component, the preparation method comprising the following steps:

[0009] A transparent substrate layer with a transparent bottom electrode is provided, and P1 scribing is performed to scribe the transparent bottom electrode.

[0010] A first carrier transport layer, a wide bandgap perovskite absorption layer and a second carrier transport layer are sequentially stacked on the transparent bottom electrode, and then P2-1 is drawn on one side parallel to P1 until the transparent bottom electrode is exposed.

[0011] A third carrier transport layer, a tunneling composite layer and a fourth carrier transport layer are sequentially stacked on the second carrier transport layer, and then P2-2 scribing is performed until the transparent bottom electrode is exposed; wherein the P2-2 scribing line and the P2-1 scribing line at least partially overlap.

[0012] A narrow bandgap perovskite absorption layer and a fifth carrier transport layer are sequentially stacked on the fourth carrier transport layer, and then P2-3 scribing is performed until the transparent bottom electrode is exposed; wherein the projection formed by the P2-3 scribing on the horizontal reference plane is located within the inner area of ​​the projection formed by the P2-2 scribing on the horizontal reference plane.

[0013] A top electrode layer is stacked on the fifth carrier transport layer, and then a P3 scribing line is performed on a side of the P2-1 scribing line away from the P1 scribing line to cut off the top electrode layer.

[0014] The present invention designs P2-1 lines, P2-2 lines and P2-3 lines, thereby retaining at least a portion of the third carrier transport layer and a portion of the narrow-bandgap perovskite absorption layer in the isolation groove, achieving side wall coverage of the tunneling composite layer, avoiding direct side contact between the subsequently formed top electrode layer and the tunneling compliance layer, effectively improving the filling factor of the stacked perovskite component, and further improving the photoelectric conversion efficiency of the stacked perovskite component.

[0015] In the present invention, “performing P2-1 scribing until the transparent bottom electrode is exposed” means scribing the first carrier transport layer, the wide bandgap perovskite absorption layer and the second carrier transport layer to expose the transparent bottom electrode. “Performing P2-2 scribing until the transparent bottom electrode is exposed” means scribing the third carrier transport layer, the tunneling recombination layer and the fourth carrier transport layer to expose the transparent bottom electrode. “Performing P2-3 scribing until the transparent bottom electrode is exposed” means scribing the narrow bandgap perovskite absorption layer and the fifth carrier transport layer.

[0016] It should be noted that the horizontal reference plane refers to an ideal plane parallel to the component placement plane.

[0017] Preferably, the method for performing the P1 scribing comprises laser scribing.

[0018] Preferably, the isolation groove formed by the P1 scribing fills the extension portion of the first carrier transport layer.

[0019] Preferably, the width of the isolation groove formed by the P2-1 scribing is 70-120 μm, for example, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm or 120 μm.

[0020] Preferably, the method for performing the P2-1 scribing includes a laser scribing method, and the specific parameters include:

[0021] The laser power is 0.3-1.5W, for example, it can be 0.3W, 0.5W, 0.7W, 1W or 1.5W, etc. The laser scribing speed is 100-1000mm / s, for example, it can be 100mm / s, 300mm / s, 500mm / s, 700mm / s, 900mm / s or 1000mm / s, etc.

[0022] Preferably, the projection of the P2-2 line on the horizontal reference plane is located within the internal area of ​​the projection of the P2-1 line on the horizontal reference plane, so that part of the inner wall of the isolation groove formed by the P2-2 line is an extension of the third carrier transport layer, and the extension of the third carrier transport layer is in contact with the transparent bottom electrode.

[0023] In the present invention, the purpose of the above limitation is to ensure that the P2-1 line width is the widest (P2-1>P2-2>P2-3), to ensure that the subsequent P2-2 line is within the P2-1 range, to retain part of the first layer SnO2 side, and to provide protection for the wide bandgap perovskite side.

[0024] Preferably, the P2-2 line is parallel to the P2-1 line.

[0025] Preferably, the width of the isolation groove formed by the P2-2 scribing is 60-110 μm, for example, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or 110 μm.

[0026] Preferably, the method for performing the P2-2 scribing includes a laser scribing method, and the specific parameters include:

[0027] The laser power is 0.3-1.5W, for example, it can be 0.3W, 0.5W, 0.7W, 1W or 1.5W, etc. The laser scribing speed is 100-1000mm / s, for example, it can be 100mm / s, 300mm / s, 500mm / s, 700mm / s, 900mm / s or 1000mm / s, etc.

[0028] Preferably, the P2-3 line is parallel to the P2-2 line.

[0029] Preferably, the width of the isolation groove formed by the P2-3 scribing is 40-90 μm, for example, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm or 90 μm.

[0030] Preferably, part of the inner wall of the isolation groove formed by the P2-3 scribing is an extension of the narrow bandgap perovskite absorption layer.

[0031] In the present invention, by retaining the extended portion of the narrow bandgap perovskite absorption layer, the tunneling composite layer and the top electrode layer are isolated, direct side contact is avoided, and the filling factor of the stacked perovskite component is effectively improved, thereby improving the photoelectric conversion efficiency of the stacked perovskite component.

[0032] Preferably, the method for performing the P2-3 scribing includes a laser scribing method, and the specific parameters include:

[0033] The laser power is 0.3-1.5W, for example, it can be 0.3W, 0.5W, 0.7W, 1W or 1.5W, etc. The laser scribing speed is 100-1000mm / s, for example, it can be 100mm / s, 300mm / s, 500mm / s, 700mm / s, 900mm / s or 1000mm / s, etc.

[0034] Preferably, the isolation groove formed by the P2-3 scribing is filled with an extension portion of the top electrode layer.

[0035] Preferably, the P3 scribe line is parallel to the P1 scribe line.

[0036] Preferably, the width of the isolation groove formed by the P3 scribing is 30-60 μm, for example, 30 μm, 40 μm, 50 μm or 60 μm.

[0037] Preferably, the method for performing the P3 scribing comprises laser scribing.

[0038] Preferably, the transparent bottom electrode comprises an ITO (indium tin oxide) layer or a FTO (fluorine-doped tin oxide) layer.

[0039] Preferably, the first carrier transport layer and the second carrier transport layer transport charges with opposite electrical properties, the second carrier transport layer and the third carrier transport layer transport charges with the same electrical properties, and the fourth carrier transport layer and the fifth carrier transport layer transport charges with opposite electrical properties.

[0040] Preferably, the first carrier transport layer is a first hole transport layer, the second carrier transport layer is a first electron transport layer, the third carrier transport layer is a second electron transport layer, the fourth carrier transport layer is a second hole transport layer, and the fifth carrier transport layer is a third electron transport layer.

[0041] Preferably, the first hole transport layer and the second hole transport layer each independently include a nickel oxide layer and / or a PEDOT:PSS layer.

[0042] Preferably, the first electron transport layer, the second electron transport layer and the third electron transport layer each independently include C 60 layer and / or SnO2 layer.

[0043] The thickness of the first carrier transport layer, the second carrier transport layer, the third carrier transport layer, the fourth carrier transport layer and the fifth carrier transport layer are each independently 5-60nm, for example, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm or 60nm.

[0044] Preferably, the preparation methods of the first hole transport layer and the second hole transport layer each independently include a physical vapor deposition method or a solution method.

[0045] Preferably, the preparation methods of the first electron transport layer, the second electron transport layer and the third electron transport layer each independently include a physical vapor deposition method or a solution method.

[0046] Preferably, the chemical formulas of the wide bandgap perovskite absorber layer and the narrow bandgap perovskite absorber layer are independently ABX3, wherein A is any one or a combination of at least two of formamidinium ions, methylamine ions or cesium ions, B is lead ions and / or tin ions, and X is a halogen ion.

[0047] Preferably, the band gap of the wide band gap perovskite absorption layer is 1.65-1.8 eV, for example, it can be 1.65 eV, 1.67 V, 1.7 eV, 1.72 eV, 1.74 eV, 1.76 eV, 1.78 eV or 1.8 eV.

[0048] Preferably, the band gap of the narrow band gap perovskite absorber layer is 1.2-1.35 eV, for example, it may be 1.2 eV, 1.22 eV, 1.25 eV, 1.27 eV, 1.3 eV, 1.32 eV or 1.35 eV.

[0049] Preferably, the wide bandgap perovskite absorption layer has a thickness of 300-600 nm, for example, 300 nm, 400 nm, 500 nm or 600 nm.

[0050] Preferably, the thickness of the narrow bandgap perovskite absorption layer is 800-1200 nm, for example, 800 nm, 900 nm, 1000 nm, 1100 nm or 1200 nm.

[0051] Preferably, the preparation methods of the wide bandgap perovskite absorption layer and the narrow bandgap perovskite absorption layer independently include any one of spin coating, blade coating, slit coating or evaporation, or a combination of at least two thereof.

[0052] Preferably, the material of the tunneling composite layer is a conductive metal oxide or a metal element. Exemplarily, the metal element may be Au or the like.

[0053] Preferably, the conductive metal oxide includes any one of ITO (indium tin oxide), IZO (indium zinc oxide) or IWO (indium tungsten oxide).

[0054] Preferably, the thickness of the tunneling composite layer is 5-15 nm, for example, 5 nm, 8 nm, 10 nm, 12 nm or 15 nm.

[0055] Preferably, the preparation method of the tunneling composite layer includes any one of magnetron sputtering, thermal evaporation or reactive plasma sputtering, or a combination of at least two of them.

[0056] Preferably, the material of the top electrode layer is metal.

[0057] Preferably, the thickness of the top electrode layer is 80-120 nm, for example, 80 nm, 90 nm, 100 nm, 110 nm or 120 nm.

[0058] Preferably, the preparation method of the top electrode layer comprises any one of thermal evaporation, magnetron sputtering or reactive plasma sputtering, or a combination of at least two of them.

[0059] In a second aspect, the present invention provides a laminated perovskite component, which is prepared by the preparation method described in the first aspect.

[0060] However, it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0062] Compared with the prior art, the present invention has the following beneficial effects:

[0063] The present invention designs P2-1 lines, P2-2 lines and P2-3 lines, thereby retaining at least a portion of the narrow-bandgap perovskite absorption layer in the isolation groove, achieving side wall coverage of the tunneling composite layer, avoiding direct side contact between the subsequently formed top electrode layer and the tunneling composite layer, and effectively improving the filling factor of the stacked perovskite component, thereby improving the photoelectric conversion efficiency of the stacked perovskite component. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 This is a process flow chart of the preparation method provided in Example 1 of the present invention.

[0065] Figure 2 This is a schematic diagram after P2-1 marking in the preparation method provided in Example 1 of the present invention.

[0066] Figure 3 This is a schematic diagram after P2-2 marking in the preparation method provided in Example 1 of the present invention.

[0067] Figure 4 This is a schematic diagram after P2-3 marking in the preparation method provided in Example 1 of the present invention.

[0068] Figure 5 This is a schematic diagram after P3 marking in the preparation method provided in Example 1 of the present invention.

[0069] Among them, 1-glass substrate; 2-transparent bottom electrode; 3-nickel oxide layer; 4-wide bandgap perovskite absorption layer; 5-first C 60 layer; 6-first SnO2 layer; 7-IWO layer; 8-PEDOT:PSS layer; 9-narrow bandgap perovskite absorption layer; 10-second C 60 layer; 11- second SnO2 layer; 12- Cu electrode layer. DETAILED DESCRIPTION

[0070] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0071] Example 1

[0072] This embodiment combines Figure 1 , Figure 2 , Figure 3 , Figure 4 and Figure 5 , provides a method for preparing a stacked perovskite component, the preparation method comprising the following steps:

[0073] (1) A glass substrate 1 with a transparent bottom electrode is provided, and a P1 line is scribed by laser scribing to cut off the transparent bottom electrode 2.

[0074] Wherein, the transparent bottom electrode 2 is a FTO layer.

[0075] (2) A nickel oxide layer 3 with a thickness of 10 nm and a wide bandgap perovskite absorption layer 4 with a thickness of 400 nm (chemical formula: FA) are sequentially stacked on the transparent bottom electrode 2 by magnetron sputtering, solution spin coating and thermal evaporation. 0.65 Cs 0.35 PbI 1.8 Br 1.2 , band gap of 1.78 eV) and a first C with a thickness of 10 nm 60 Layer 5 is formed, and then a laser scribing method is used to perform P2-1 scribing on the parallel side of P1 scribing line until the transparent bottom electrode 2 is exposed.

[0076] The isolation groove formed by P1 scribing fills the extension of the nickel oxide layer 3; the width of the isolation groove formed by P2-1 scribing is 100 μm; the specific parameters of the laser scribing method include: the laser power is 1 W, and the laser scribing speed is 500 mm / s.

[0077] (3) Atomic layer deposition, magnetron sputtering and solution spin coating were used in sequence to deposit the first C 60 A first SnO2 layer 6 with a thickness of 60 nm, an IWO layer 7 with a thickness of 10 nm and a PEDOT:PSS layer 8 with a thickness of 10 nm are sequentially stacked on the layer 5, and then a P2-2 line is scribed by laser scribing until the transparent bottom electrode 2 is exposed.

[0078] Among them, the projection formed by the P2-2 line on the horizontal reference plane is located within the internal area of ​​the projection formed by the P2-1 line on the horizontal reference plane, so that part of the inner wall of the isolation groove formed by the P2-2 line is an extension of the first SnO2 layer 6, and the extension of the first SnO2 layer 6 is in contact with the transparent bottom electrode 2; the P2-2 line is parallel to the P2-1 line; the width of the isolation groove formed by the P2-2 line is 80μm; the specific parameters of the laser scribing method include: the laser power is 1W, and the laser scribing speed is 500mm / s.

[0079] (4) A narrow bandgap perovskite absorption layer 9 (chemical formula: FA) with a thickness of 1000 nm was sequentially stacked on the PEDOT:PSS layer 8 by solution spin coating, thermal evaporation and atomic layer deposition respectively.0.7 MA 0.3 Pb 0.5 Sn 0.5 I3, band gap 1.22eV), a second C with a thickness of 10nm 60 Layer 10 and a second SnO2 layer 11 with a thickness of 15 nm are then formed, and P2-3 lines are scribed using a laser scribing method until the transparent bottom electrode 2 is exposed.

[0080] Among them, the projection formed by the P2-3 line on the horizontal reference plane is located within the internal area of ​​the projection formed by the P2-2 line on the horizontal reference plane; the P2-3 line is parallel to the P2-2 line; the width of the isolation groove formed by the P2-3 line is 50μm; part of the inner wall of the isolation groove formed by the P2-3 line is an extension of the narrow bandgap perovskite absorption layer 9; the center positions of the P2-1 line, the P2-2 line and the P2-3 line are consistent; the specific parameters of the laser scribing method include: the laser power is 1.2W, and the laser scribing speed is 500mm / s.

[0081] (5) A Cu layer 12 with a thickness of 100 nm is formed on the second SnO2 layer 11 by thermal evaporation, and then a P3 line is made on the side of the P2-1 line away from the P1 line by laser scribing to cut off the Cu layer 12, and finally a Cu layer with an actual area of ​​20.25 cm is obtained. 2 , a stacked perovskite component consisting of 8 sub-cells connected in series.

[0082] The isolation groove formed by the P2-3 scribing line is filled with the extension portion of the Cu layer 12; the P3 scribing line is parallel to the P1 scribing line; and the width of the isolation groove formed by the P3 scribing line is 50 μm.

[0083] Example 2

[0084] This embodiment provides a method for preparing a laminated perovskite component, and the preparation method comprises the following steps:

[0085] (1) Provide a glass substrate with a transparent bottom electrode, and use a laser scribing method to scribe the P1 line to cut the transparent bottom electrode.

[0086] Among them, the transparent bottom electrode is a FTO layer.

[0087] (2) Magnetron sputtering, solution spin coating and thermal evaporation were used to sequentially stack a nickel oxide layer with a thickness of 8 nm and a wide bandgap perovskite absorption layer with a thickness of 300 nm on the transparent bottom electrode. 0.65 Cs 0.35 PbI 1.8 Br 1.2 , band gap of 1.78 eV) and a first C 60layer, and then use laser scribing to perform P2-1 scribing on the parallel side of P1 scribing until the transparent bottom electrode is exposed.

[0088] The isolation groove formed by P1 scribing is filled with the extension of the nickel oxide layer; the width of the isolation groove formed by P2-1 scribing is 70 μm; the specific parameters of the laser scribing method include: the laser power is 0.3 W, and the laser scribing speed is 100 mm / s.

[0089] (3) Atomic layer deposition, magnetron sputtering and solution spin coating were used in sequence to deposit the first C 60 A first SnO2 layer with a thickness of 60 nm, an Au layer with a thickness of 5 nm, and a PEDOT:PSS layer with a thickness of 10 nm are sequentially stacked on the layers, and then P2-2 lines are scribed by laser scribing until the transparent bottom electrode is exposed.

[0090] Among them, the projection formed by the P2-2 line on the horizontal reference plane is located within the internal area of ​​the projection formed by the P2-1 line on the horizontal reference plane, so that part of the inner wall of the isolation groove formed by the P2-2 line is an extension of the first SnO2 layer, and the extension of the first SnO2 layer is in contact with the transparent bottom electrode; the P2-2 line is parallel to the P2-1 line; the width of the isolation groove formed by the P2-2 line is 60μm; the specific parameters of the laser scribing method include: the laser power is 0.3W, and the laser scribing speed is 100mm / s.

[0091] (4) A narrow bandgap perovskite absorption layer (chemical formula: FA) with a thickness of 800 nm was sequentially stacked on the PEDOT:PSS layer by solution spin coating, thermal evaporation, and atomic layer deposition. 0.7 MA 0.3 Pb 0.5 Sn 0.5 I3, band gap 1.22eV), and a second C with a thickness of 8nm 60 layer and a second SnO2 layer with a thickness of 10 nm, and then P2-3 lines are scribed by laser scribing until the transparent bottom electrode is exposed.

[0092] Among them, the projection formed by the P2-3 marking line on the horizontal reference plane is located within the internal area of ​​the projection formed by the P2-2 marking line on the horizontal reference plane; the P2-3 marking line is parallel to the P2-2 marking line; the width of the isolation groove formed by the P2-3 marking line is 50μm; part of the inner wall of the isolation groove formed by the P2-3 marking line is an extension of the narrow bandgap perovskite absorption layer; the center positions of the P2-1 marking line, the P2-2 marking line and the P2-3 marking line are consistent; the specific parameters of the laser scribing method include: the laser power is 0.3W, and the laser scribing speed is 100mm / s.

[0093] (5) A Cu layer with a thickness of 80 nm was formed on the second SnO2 layer by thermal evaporation, and then a P3 line was made on the side of the P2-1 line away from the P1 line by laser scribing to cut through the Cu layer, and finally a Cu layer with an actual area of ​​20.25 cm was obtained. 2 , a stacked perovskite component consisting of 8 sub-cells connected in series.

[0094] The isolation groove formed by the P2-3 scribing line is filled with the extension of the Cu layer; the P3 scribing line is parallel to the P1 scribing line; and the width of the isolation groove formed by the P3 scribing line is 30 μm.

[0095] Example 3

[0096] This embodiment provides a method for preparing a laminated perovskite component, and the preparation method comprises the following steps:

[0097] (1) Provide a glass substrate with a transparent bottom electrode, and use a laser scribing method to scribe the P1 line to cut the transparent bottom electrode.

[0098] Among them, the transparent bottom electrode is a FTO layer.

[0099] (2) Magnetron sputtering, solution spin coating and thermal evaporation were used to sequentially stack a nickel oxide layer with a thickness of 10 nm and a wide bandgap perovskite absorption layer with a thickness of 600 nm on the transparent bottom electrode. 0.65 Cs 0.35 PbI 1.8 Br 1.2 , band gap of 1.78 eV) and a first C with a thickness of 15 nm 60 layer, and then use laser scribing to perform P2-1 scribing on the parallel side of P1 scribing until the transparent bottom electrode is exposed.

[0100] The isolation groove formed by P1 scribing is filled with the extension of the nickel oxide layer; the width of the isolation groove formed by P2-1 scribing is 120 μm; the specific parameters of the laser scribing method include: the laser power is 1.5 W, and the laser scribing speed is 1000 mm / s.

[0101] (3) Atomic layer deposition, magnetron sputtering and solution spin coating were used in sequence to deposit the first C 60 A first SnO2 layer with a thickness of 60 nm, an IWO layer with a thickness of 15 nm, and a PEDOT:PSS layer with a thickness of 10 nm are sequentially stacked on the layers, and then P2-2 lines are scribed by laser scribing until the transparent bottom electrode is exposed.

[0102] Among them, the projection formed by the P2-2 line on the horizontal reference plane is located within the internal area of ​​the projection formed by the P2-1 line on the horizontal reference plane, so that part of the inner wall of the isolation groove formed by the P2-2 line is an extension of the first SnO2 layer, and the extension of the first SnO2 layer is in contact with the transparent bottom electrode; the P2-2 line is parallel to the P2-1 line; the width of the isolation groove formed by the P2-2 line is 90μm; the specific parameters of the laser scribing method include: the laser power is 1.5W, and the laser scribing speed is 1000mm / s.

[0103] (4) A narrow bandgap perovskite absorption layer (chemical formula: FA) with a thickness of 1200 nm was sequentially stacked on the PEDOT:PSS layer by solution spin coating, thermal evaporation, and atomic layer deposition. 0.7 MA 0.3 Pb 0.5 Sn 0.5 I3, band gap 1.22eV), a second C with a thickness of 15nm 60 layer and a second SnO2 layer with a thickness of 15 nm, and then P2-3 lines are scribed by laser scribing until the transparent bottom electrode is exposed.

[0104] Among them, the projection formed by the P2-3 marking line on the horizontal reference plane is located within the internal area of ​​the projection formed by the P2-2 marking line on the horizontal reference plane; the P2-3 marking line is parallel to the P2-2 marking line; the width of the isolation groove formed by the P2-3 marking line is 80μm; part of the inner wall of the isolation groove formed by the P2-3 marking line is an extension of the narrow bandgap perovskite absorption layer; the center positions of the P2-1 marking line, the P2-2 marking line and the P2-3 marking line are consistent; the specific parameters of the laser scribing method include: the laser power is 1.5W, and the laser scribing speed is 1000mm / s.

[0105] (5) A 120 nm thick Cu layer was formed on the second SnO2 layer by thermal evaporation, and then a P3 line was made on the side of the P2-1 line away from the P1 line by laser scribing to cut through the Cu layer, and finally a 20.25 cm 2 , a stacked perovskite component consisting of 8 sub-cells connected in series.

[0106] The isolation groove formed by the P2-3 scribing line is filled with the extension of the Cu layer; the P3 scribing line is parallel to the P1 scribing line; and the width of the isolation groove formed by the P3 scribing line is 60 μm.

[0107] Example 4

[0108] The difference between this embodiment and the first embodiment is that the P2-2 scribing line and the P2-1 scribing line completely overlap, that is, the width of the isolation groove formed by the P2-2 scribing line is equal to the width of the isolation groove formed by the P2-1 scribing line.

[0109] The rest of the preparation methods and parameters were the same as those in Example 1.

[0110] Comparative Example 1

[0111] The difference between this comparative example and Example 1 is that the P2-1 marking line, the P2-2 marking line and the P2-3 marking line completely overlap, that is, the width of the isolation groove formed by the P2-3 marking line, the width of the isolation groove formed by the P2-2 marking line and the width of the isolation groove formed by the P2-1 marking line are equal.

[0112] The rest of the preparation methods and parameters were the same as those in Example 1.

[0113] Comparative Example 2

[0114] The difference between this comparative example and Example 1 is that P2-1 scribing and P2-2 scribing are not performed.

[0115] The rest of the preparation methods and parameters were the same as those in Example 1.

[0116] Performance Testing

[0117] The photoelectric performance of the stacked perovskite components provided in the above embodiments and comparative examples was tested.

[0118] The test conditions include: using a dual-light source solar spectrum simulator.

[0119] The test results are shown in Table 1.

[0120] Table 1

[0121]

[0122]

[0123] analyze:

[0124] In summary, the present invention retains at least a portion of the third carrier transport layer and a portion of the narrow bandgap perovskite absorption layer in the isolation groove by designing the P2-1 line, the P2-2 line and the P2-3 line, thereby achieving side wall coverage of the tunneling composite layer, avoiding direct side contact between the subsequently formed top electrode layer and the tunneling compliance layer, and effectively improving the filling factor of the stacked perovskite component, thereby improving the photoelectric conversion efficiency of the stacked perovskite component.

[0125] It can be seen from Examples 1 and 4 that if the width of the isolation groove formed by P2-2 scribing is equal to the width of the isolation groove formed by P2-1 scribing, P2-2 completely removes the side of the first SnO2 layer, exposing the wide bandgap side, causing the narrow bandgap perovskite deposition process to directly contact the bottom wide bandgap side, causing part of the wide bandgap perovskite to dissolve, resulting in a decrease in the fill factor and a decrease in device performance.

[0126] It can be seen from Example 1 and Comparative Example 1 that if the P2-1 line, the P2-2 line and the P2-3 line completely overlap, direct side contact between the subsequently formed top electrode layer and the tunneling compliance layer cannot be avoided, resulting in decreased component performance.

[0127] It can be seen from Example 1 and Comparative Example 2 that if P2-1 scribing and P2-2 scribing are not performed, direct side contact between the subsequently formed top electrode layer and the tunneling compliance layer cannot be avoided, resulting in degradation of component performance.

[0128] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a laminated perovskite component, characterized in that: The preparation method comprises the following steps: Providing a transparent substrate layer with a transparent bottom electrode, performing P1 scribing, and scribing the transparent bottom electrode; A first carrier transport layer, a wide bandgap perovskite absorption layer, and a second carrier transport layer are sequentially stacked on the transparent bottom electrode, and then a P2-1 line is performed on a side parallel to the P1 line until the transparent bottom electrode is exposed; A third carrier transport layer, a tunneling composite layer and a fourth carrier transport layer are sequentially stacked on the second carrier transport layer, and then P2-2 scribing is performed until the transparent bottom electrode is exposed; wherein the P2-2 scribing line and the P2-1 scribing line at least partially overlap; A narrow bandgap perovskite absorption layer and a fifth carrier transport layer are sequentially stacked on the fourth carrier transport layer, and then P2-3 scribing is performed until the transparent bottom electrode is exposed; wherein the projection formed by the P2-3 scribing line on the horizontal reference plane is located within the inner region of the projection formed by the P2-2 scribing line on the horizontal reference plane; A top electrode layer is stacked on the fifth carrier transport layer, and then a P3 scribing line is performed on a side of the P2-1 scribing line away from the P1 scribing line to cut off the top electrode layer.

2. The preparation method according to claim 1, characterized in that: The method for performing the P1 scribing includes a laser scribing method; Preferably, the isolation groove formed by the P1 scribing fills the extension portion of the first carrier transport layer.

3. The preparation method according to claim 1, characterized in that: The width of the isolation groove formed by the P2-1 scribing is 70-120 μm; Preferably, the method for performing the P2-1 scribing includes a laser scribing method, and the specific parameters include: The laser power is 0.3-1.5W, and the laser scribing speed is 100-1000mm / s.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The projection of the P2-2 scribe line on the horizontal reference plane is located within the inner region of the projection of the P2-1 scribe line on the horizontal reference plane, so that part of the inner wall of the isolation groove formed by the P2-2 scribe line is an extension of the third carrier transport layer, and the extension of the third carrier transport layer is in contact with the transparent bottom electrode; Preferably, the P2-2 line is parallel to the P2-1 line; Preferably, the width of the isolation groove formed by the P2-2 scribing is 60-110 μm; Preferably, the method for performing the P2-2 scribing includes a laser scribing method, and the specific parameters include: The laser power is 0.3-1.5W, and the laser scribing speed is 100-1000mm / s.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The P2-3 line is parallel to the P2-2 line; Preferably, the width of the isolation groove formed by the P2-3 scribing is 40-90 μm; Preferably, part of the inner wall of the isolation groove formed by the P2-3 scribing is an extension of the narrow bandgap perovskite absorption layer; Preferably, the method for performing the P2-3 scribing includes a laser scribing method, and the specific parameters include: The laser power is 0.3-1.5W, and the laser scribing speed is 100-1000mm / s.

6. The preparation method according to any one of claims 1 to 5, characterized in that: Filling the extension of the top electrode layer in the isolation groove formed by the P2-3 scribing; Preferably, the P3 scribe line is parallel to the P1 scribe line; Preferably, the width of the isolation groove formed by the P3 scribing is 30-60 μm; Preferably, the method for performing the P3 scribing comprises laser scribing.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The transparent bottom electrode comprises an ITO layer or a FTO layer; Preferably, the first carrier transport layer and the second carrier transport layer transport charges with opposite electrical properties, the second carrier transport layer and the third carrier transport layer transport charges with the same electrical properties, and the fourth carrier transport layer and the fifth carrier transport layer transport charges with opposite electrical properties; Preferably, the first carrier transport layer is a first hole transport layer, the second carrier transport layer is a first electron transport layer, the third carrier transport layer is a second electron transport layer, the fourth carrier transport layer is a second hole transport layer, and the fifth carrier transport layer is a third electron transport layer; Preferably, the first hole transport layer and the second hole transport layer each independently comprise a nickel oxide layer and / or a PEDOT:PSS layer; Preferably, the first electron transport layer, the second electron transport layer and the third electron transport layer each independently include C 60 layer and / or SnO2 layer; The thickness of the first carrier transport layer, the second carrier transport layer, the third carrier transport layer, the fourth carrier transport layer and the fifth carrier transport layer are each independently 5-60 nm; Preferably, the preparation methods of the first hole transport layer and the second hole transport layer each independently include a physical vapor deposition method or a solution method; Preferably, the preparation methods of the first electron transport layer, the second electron transport layer and the third electron transport layer each independently include a physical vapor deposition method or a solution method.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The chemical formula of the wide bandgap perovskite absorption layer and the narrow bandgap perovskite absorption layer are independently ABX3, wherein A is any one or a combination of at least two of formamidinium ions, methylamine ions or cesium ions, B is lead ions and / or tin ions, and X is a halogen ion; Preferably, the band gap of the wide band gap perovskite absorber layer is 1.65-1.8 eV; Preferably, the band gap of the narrow band gap perovskite absorber layer is 1.2-1.35 eV; Preferably, the wide bandgap perovskite absorption layer has a thickness of 300-600 nm; Preferably, the thickness of the narrow bandgap perovskite absorption layer is 800-1200 nm; Preferably, the preparation methods of the wide bandgap perovskite absorption layer and the narrow bandgap perovskite absorption layer independently include any one of spin coating, blade coating, slit coating or evaporation, or a combination of at least two thereof.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The material of the tunneling composite layer is a conductive metal oxide or a metal element; Preferably, the thickness of the tunneling composite layer is 5-15 nm; Preferably, the preparation method of the tunneling composite layer includes any one of magnetron sputtering, thermal evaporation or reactive plasma sputtering, or a combination of at least two thereof; Preferably, the material of the top electrode layer is metal; Preferably, the thickness of the top electrode layer is 80-120 nm; Preferably, the preparation method of the top electrode layer comprises any one of thermal evaporation, magnetron sputtering or reactive plasma sputtering, or a combination of at least two of them.

10. A laminated perovskite component, characterized in that: The stacked perovskite component is prepared by the preparation method according to any one of claims 1 to 9.